2015
DOI: 10.1007/s00181-015-0945-8
|View full text |Cite
|
Sign up to set email alerts
|

Internationalization choices: an ordered probit analysis at industry level

Abstract: Trade theory traces back different patterns of internationalization to heterogeneity between firms, measured both through differences in productivity levels and size. In this paper we analyze the link between heterogeneity within sectors and internationalization choices, namely trade and foreign direct investments (FDI) for a large sample of countries and industries between 1994 and 2004. The focus of our paper is on the role played by average productivity level and the distribution of firms by size in explain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 47 publications
1
5
0
Order By: Relevance
“…To the best of our knowledge, our analysis is the first to focus on the impact of the distribution of banks by asset size on the internationalization of the banking sector. In this sense, we extend the insights on the impact of firm size on international trade flows and FDIs in the manufacturing sector recently found by (Barba Navaretti et al , 2015, andPietrovito et al, 2013) to the cross-border activities of banks. Our results have straightforward but important policy implications, confirming that larger banks have a disproportionally higher impact on financial globalization, therefore being a channel for both risk diversification opportunities and, yet, higher risks of contagion.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…To the best of our knowledge, our analysis is the first to focus on the impact of the distribution of banks by asset size on the internationalization of the banking sector. In this sense, we extend the insights on the impact of firm size on international trade flows and FDIs in the manufacturing sector recently found by (Barba Navaretti et al , 2015, andPietrovito et al, 2013) to the cross-border activities of banks. Our results have straightforward but important policy implications, confirming that larger banks have a disproportionally higher impact on financial globalization, therefore being a channel for both risk diversification opportunities and, yet, higher risks of contagion.…”
Section: Discussionsupporting
confidence: 79%
“…Interestingly, adopting the framework of gravity equations, Barba Navaretti et al (2015) and Pietrovito et al (2013) have recently shown that it is not only the average firm size that matters, but also higher moments measuring the asymmetry of the distribution by size, such as skewness. While the same case can presumably be made for financial transactions, the empirical literature on the the patterns of cross-border interbank integration has so far ignored the role of the distribution of financial institutions by their size.…”
Section: Introductionmentioning
confidence: 99%
“…De Jong and Vermeulen (2006) identify significant variations among 1250 small firms across seven industries: manufacturing, construction, wholesale and transport, retail, hotel and catering, knowledge intensive services, and financial services. A study of 57 manufacturing industries across 91 destination countries shows that sectors characterised by larger and more dispersed firm sales are more likely to be international (Pietrovito et al, 2016). To make our findings comparable with extant research, we control the internationalisation of new ventures across seven industries: health care, technology, consumer services, finance, consumer goods, industrials and utilities.…”
Section: Environment Control Variables: Competition and Industrymentioning
confidence: 69%
“…FDI plays a relevant role in territorial economic connectivity, defined as the degree of inward and outward openness that shapes the local churn of skills, capabilities, production systems and economic activities (Crescenzi et al, 2014). The rich literature on the role of FDI in socio-economic development concludes that FDI is a fast route for companies to expand their business in international markets (Crescenzi et al, 2021;EC, 2020b;Hanousek, 2011;Pietrovito et al, 2016). Notwithstanding the potentially detrimental effects on employment in home economies (Crescenzi, Ganau, & Storper, 2022), FDI increases the capital stock, access to innovations, technology transfers, improvements in skills and new job opportunities in the host country (Gonzalez et al, 2017;Harding & Javorcik, 2011).…”
Section: Fdimentioning
confidence: 99%